THU0297 SERIOUS INFECTIONS IN 134 PATIENTS WITH GIANT CELL ARTERITIS WITH TOCILIZUMAB IN CLINICAL PRACTICE. FREQUENCY, TYPE AND CLINICAL ASSOCIATIONS. (2nd June 2020) - Calderón-Goercke, M.; Prieto-Peña, D.; Castañeda, S.; Moriano, C.; Becerra-Fernández, E.; Revenga, M.; Alvarez-Rivas, N.; Galisteo, C.; Prior-Español, Á.; Galindez, E.; Hidalgo, C.; Manrique Arija, S.; et al.
Abstract : Background: Infections are the most common adverse event of Tocilizumab (TCZ) in Giant Cell Arteritis (GCA). In GiACTA study (1), serious infections were observed in 7% (9.6/100 patient-years) of patients who received TCZ weekly. Randomized clinical trials (RCTs) are conducted under highly standardized design excluding some real-world patients. Therefore, adverse events may be underestimated in RCTs. In our series of real-life, serious infections occurred in 11.9% (10.6/100 patient-years) (2). Objectives: In a wide series of GCA of clinical practice treated with TCZ, we assess the frequency, type and predisposing factors of serious infections. Methods: Multicenter study of 134 patients diagnosed with GCA, all of them refractory to conventional therapy, treated with TCZ. Serious infection was considered when a life-threatening infection, fatal, or requiring hospitalization occurred, intravenous antibiotics were required, or the infectious process led to persistent or significant disability. Results: 16 of 134 (11.9%, 10.6/100 patient-years) patients developed serious infections during follow-up. The most frequent infections were pneumonia (n=4), urinary tract infection (n=4), and facial herpes zoster (n=2). At TCZ onset, serious infections were more frequent in older patients (74.3±9.6 vs 72.9±8.7 years), with a longer GCA evolution (20 [4.3-45.6] vs 13 [5-29.3] months), with visual manifestations (43.75% vs 17.8%) and a higher dose of prednisone at TCZ onset (30.4±15.5 vs 21.1±16.1 mg/day) (TABLE). Presence of comorbidities were similar in both groups. 13 of the 16 patients who had infections received a dose of prednisone greater than 15 mg/day (16.3/100 patient-years) compared to 3 patients under treatment with less than 15 mg/day of prednisone (4.2/100 patient-years). Conclusion: The age, GCA duration, ocular involvement and the dose of glucocorticoids, at TCZ onset, seem to be predisposing factors related to an increased risk of developing serious infections in GCA patients. References: [1]Stone JH, et al. N Engl J Med. 2017; 377:317-28. [2]Calderón-Goercke M et al. Semin Arthritis Rheum 2019 Aug;49(1): 126-135. Disclosure of Interests: Monica Calderón-Goercke: None declared, D. Prieto-Peña: None declared, Santos Castañeda: None declared, Clara Moriano: None declared, Elena Becerra-Fernández: None declared, Marcelino Revenga: None declared, Noelia Alvarez-Rivas: None declared, Carles Galisteo: None declared, Águeda Prior-Español: None declared, E. Galindez: None declared, Cristina Hidalgo: None declared, Sara Manrique Arija: None declared, Eugenio de Miguel Grant/research support from: Yes (Abbvie, Novartis, Pfizer), Consultant of: Yes (Abbvie, Novartis, Pfizer), Paid instructor for: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Speakers bureau: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Eva Salgado-Pérez: None declared, Vicente Aldasoro Speakers bureau: Roche, Abbvie, MSD, UCB, Pfizer, Menarini, Grunenthal, Gebro, Novartis, Janssen, Ignacio Villa-Blanco Consultant of: UCB, Speakers bureau: Novartis, MSD, Lilly, Susana Romero-Yuste: None declared, J. Narváez: None declared, Catalina Gomez-Arango: None declared, Eva Perez-Pampín: None declared, Rafael Melero: None declared, Francisca Sivera: None declared, Carlos Fernández-Díaz Speakers bureau: Brystol Meyers Squibb, Alejandro Olive: None declared, María Álvarez del Buergo: None declared, Luisa Marena Rojas: None declared, Carlos Fernández-López: None declared, Francisco Navarro: None declared, Enrique Raya: None declared, Beatriz Arca: None declared, Roser Solans-Laqué: None declared, Arantxa Conesa: None declared, Carlos Vázquez: None declared, Jose Andrés Román-Ivorra: None declared, Pau Lluch: None declared, Paloma Vela-Casasempere: None declared, Carmen Torres-Martín: None declared, Juan Carlos Nieto Speakers bureau: Pfizer, Abbvie, MSD, Novartis, Janssen, Lilly, Nordic Pharma, BMS, Gebro, FAES Farma, Roche, Sanofi, Carmen Ordas-Calvo: None declared, Cristina Luna-Gomez: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Nagore Fernández-Llanio: None declared, Antonio García: None declared, Carmen González-Vela: None declared, Javier García-Fernández: None declared, Patricia Vicente-Gómez: None declared, Ángel García-Manzanares: None declared, Norberto Ortego: None declared, Francisco Ortiz-Sanjuán: None declared, Montserrat Corteguera: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Ricardo Blanco Grant/research support from: AbbVie, MSD, and Roche, Speakers bureau: AbbVie, Pfizer, Roche, Bristol-Myers, Janssen, and MSD